The Judiciary in Islamic Law, Palestinian Legislation, and Guarantees of Its Independence - Hamad, Ahmed M A; Anuar, Haslinda binti Mohd.; Halim, Rohizan binti (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The contemplating the constitutional and legal system of democratic countries, they unite on the principle of the independence of the judiciary until it became a constitutional principle related to the protection of human rights, which is a natural effect of the existence of a judiciary that stands on an equal footing with the legislative and executive authorities. The principle of the independence of the judiciary is considered the first principle of the general principles governing the work of the judiciary. The independence of the judiciary leads to its immunity by preventing the executive authority from intruding and interfering in its affairs and its work. The importance of this study is that it will clarify the extent to which the principle of the independence of the judiciary is applied in Islamic law compared to Palestinian legislation and the guarantees of this principle. To achieve the objective of this paper, legal socio-legal research was adopted using the qualitative approach to analyse relevant Islamic law and Palestinian legislative texts. The study concluded that the administration and structure of the judiciary in Islamic law differs from Palestinian legislation in terms of the extent of application of the principle of the independence of the judiciary.